A decade of experience with rotavirus vaccination in the United States - vaccine uptake, effectiveness, and impact - Talia Pindyck; Jacqueline E Tate; Umesh D Parashar (Taylor & Francis Group, 2018)
Introduction: Prior to 2006, nearly every U.S. child was infected with rotavirus by 5 years of age, and rotavirus was the leading cause of severe childhood gastroenteritis. In February 2006 and June 2008, the Advisory Committee on Immunization Practices recommended a live attenuated pentavalent rotavirus vaccine (RV5) and a monovalent rotavirus vaccine (RV1), respectively, for routine vaccination of infants in the United States. Areas covered: We reviewed U.S. data on coverage, vaccine effectiveness (VE), and vaccine impact from 2006 to 2017. National rotavirus vaccine coverage estimates increased since vaccine introduction but plateaued at 71-75% in 2013-2015, a level 15-20% lower than that of other routine childhood vaccines. Pooled VE of full series RV5 and RV1 against rotavirus-associated hospitalizations and emergency department visits were 84% (95% CI: 80-87%) and 83% (95% CI: 72-89%), respectively. Vaccine introduction resulted in a median decline in rotavirus-associated hospitalizations and emergency department visits of 80% and 57%, respectively, along with indirect protection of unvaccinated age groups and a decrease in health-care costs. A biennial pattern in rotavirus detection emerged post-vaccine implementation. Expert Commentary: The increasing use of rotavirus vaccines has substantially diminished the burden and changed the epidemiology of rotavirus disease in U.S. children; efforts to increase rotavirus vaccine coverage should continue.